Further observations on a bilateral IRVAN syndrome case (2019)
Purpose: Reporting clinical features of the late course of the disease after long-term follow-up in a bilaterally affected patient with idiopathic retinitis, vasculitis, retinal aneurysms and neuroretinitis (IRVAN) and new peripheral retinal findings on wide-field angiography and multimodal imaging. Methods: This was a retrospective observational study, based on current diagnostic studies including wide-field fluorescein angiography, optical coherence tomography (OCT) and treatment of aneurysms with argon laser photocoagulation. Results: A 21-year-old female with bilateral IRVAN syndrome—stage 2 in the right eye and stage 3 in the left eye—previously treated bilaterally with laser photocoagulation for retinal macroaneurysms and ischemic areas between 1985 and 1992. Follow-up interrupted on two occasions, with subsequent fundus re-examinations confirming the prevention of retinal neovascularization in both eyes, as recently evidenced on wide-field angiography. Conclusions: A case of bilateral IRVAN disease with multiple retinal aneurysms, neuroretinitis and peripheral capillary nonperfusion successfully treated with laser photocoagulation, maintaining normal visual acuity in one eye and preventing retinal neovascular complications. © 2018, Springer Science+Business Media B.V., part of Springer Nature.